Effect of teaching races for understanding in youth sailing on performance, knowledge, and adherence - Morales-Belando, M. T.; Arias-Estero, J. L. (Research Quarterly for Exercise and Sport, 2017)
Purpose: The purpose of this study was to know whether an intervention using an adaptation of the teaching games for understanding approach (named teaching races for understanding [TRfU]) led participants to improve skill execution, decision making, race performance, race involvement, race knowledge, enjoyment, intention to continue practicing sailing, and perceived competence. Method: Participants were 67 children from a randomly selected sailing school (Mage = 9.32 years, SD = 2.60 years) and 2 coaches. We designed and validated the TRfU lessons, and 1 coach was trained in the approach. The TRfU group participated in 11 lessons. This study followed a mixed-methods data approach. Quantitative data were evaluated using a quasiexperimental pretest-posttest design with a control group. The intervention consisted of teaching sailing using the TRfU approach. Children and coaches` perceptions were evaluated through an interview on completion of the study. Data were collected using an adaptation of the Game Performance Assessment Instrument, a knowledge questionnaire, 2 psychological scales, and interviews with children and coaches. Results: The TRfU group showed statistically significant improvements in skill execution, decision making, and race performance compared with the control group, as well as significant improvements in race involvement, race knowledge, and enjoyment (ES = 0.64-2.63). Conclusion: Teaching races for understanding can be used in sailing to improve students` capacity to reflect and connect theoretical knowledge with their motor performance in the race.